Lysozyme content in mixed saliva in the dynamics of treatment of patients with chronic odontogenic maxillary sinusitis in the presence of galvanic pathology in the oral cavity - Tymofeyev О. О.; Cherednichenko А. М. (Actual Dentistry, 2024)
Purpose: to determine the level of lysozyme in mixed saliva in the dynamics of treatment of patients with chronic odontogenic maxillary sinusitis in the presence of galvanic pathology in the oral cavity. Methods: 56 examined with chronic odontogenic maxillary sinusitis were divided into two observation groups, who underwent immunological and general clinical examination methods. Results: 28 patients with chronic odontogenic maxillary sinusitis, no changes in the level of lysozyme in mixed saliva were observed in the presence of galvanism (compensated and decompensated forms) in the oral cavity. 28 patients with a concomitant disease in the oral cavity, galvanism (atypical and typical forms) was found to be a long-term decrease in the level of lysozyme in mixed saliva. Conclusions: Based on the examination of 56 patients with chronic odontogenic maxillary sinusitis in the presence of galvanic pathology in the oral cavity, it was found that in the case of galvanosis, there is a decrease in local nonspecific resistance of the body, that is, a temporary immunodeficiency, which leads to the development of inflammatory complications in the periosteal soft tissues and in the bone wound of the jaw.